Smart Walking Stick for Visually Impaired People - Gia Hoang Phan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Detecting obstacles is always a difficult task for visually impaired people when they move. External guidance such as human, trained dogs, or white cane, hence, a blind stick plays an essential role in the decision making of blind people. Due to its low cost, the white cane is often used by visually impaired people. However, traditional white canes cannot accurately detect obstacles above the knee level or at a distance beyond the white cane’s length. Our goal is to create an affordable, smart blind stick that can help blind people to navigate. The device consists of an ultrasonic sensor and infrared sensors to detect obstacles in front of the blind user and a vibration motor + buzzer for alarm. One of the biggest challenges for blind people when they move inside the house is to go up and downstairs. We aim to address the challenge by integrating into the blind stick a function that alarms users in the staircase presence. Moreover, this device also has a built-in GPS module that allows the device’s and its user’s location to be tracked and displayed on a smartphone app, a desirable feature for many families of blind people. Ultrasonic and infrared sensors allowed the smart blind stick to detect obstacles at a distance from 5 to 150 cm from the user. Moreover, with a built-in GPS module, it was easy to identify the stick-on smartphone location, which made the searching location of a blind user much easier. This paper presented a design and implementation of an intelligent blind stick for blind people with several advantages, including low cost, capability to detect obstacles above knee level, staircase detection, location tracking via smartphone, etc. However, more tests need to be conducted to determine its accuracy and reliability in real-world settings.